2017
DOI: 10.24036/02017616441-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kontrol Diri dengan Perilaku Membolos Siswa

Abstract: The purpose of this research to describe self control and truant behavior students and examine the relationship between self control with the behavior of truant students. This research applied quantitative method and descriptive correlational design, with a sample of 234 students, that drawn by Propotional Stratified Random Sampling technique. The instrument of this research was a scale of Likert model. Hypothesis testing of research using the formula Pearson Product Moment Correlation with SPSS for mindows re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…Research result Olivia, (2017) it was found that there was a relationship between self-control and truancy behavior of class X vocational high school Country 1 Ngasem School year 2016/2017. Than, research result (Putri, Daharnis, & Zikra, 2017) proves that there is a significant negative relationship between selfcontrol and student truancy behavior. Weak self-control of students can be seen from the results of the study Astari & Widagda K., (2014), there are 25.06% students have moderate self control and 15.93% students have low self control.…”
Section: Introductionmentioning
confidence: 90%
“…Research result Olivia, (2017) it was found that there was a relationship between self-control and truancy behavior of class X vocational high school Country 1 Ngasem School year 2016/2017. Than, research result (Putri, Daharnis, & Zikra, 2017) proves that there is a significant negative relationship between selfcontrol and student truancy behavior. Weak self-control of students can be seen from the results of the study Astari & Widagda K., (2014), there are 25.06% students have moderate self control and 15.93% students have low self control.…”
Section: Introductionmentioning
confidence: 90%
“…Rasa kontrol yang ada pada diri seorang individu muncul manakala individu tersebut mampu merencanakan membimbing serta mengatur tindakan ke arah yang lebih baik. Adapun indikator dari sense of control menurut Putri et al (2017) terdapat 6 indikator diantaranya yaitu kemampuan mengendalikan perhatian, menahan diri,…”
Section: Sense Of Controlunclassified
“…Kondisi kontrol diri yang tidak baik membuat remaja menjadi merasa tidak berharga, tidak yakin dengan dirinya, dan lebih banyak mengalami kecemasan dan ketakutan dalam hidup. Hal ini bisa dihentikan dan dicegah dengan cara individu ikut serta dalam kegiatn kelompok dan berbaur dengan lingkungan, kegiatan ini menjadi suatu proses belajar yang baik bagi remaja dalam mengendalikan diri sehingga kontol dirinya semakin baik dari segi pikiran, keputusan dan tindakan karena ada proses belajar yang diperoleh (M. S. Putri et al, 2017).…”
Section: Hasil Dan Pembahasanunclassified